Inhibitory Effects of Novel Diarylheptanoids and Other Constituents of the Rhizomes of Curcuma singularis on the Catalytic Activity of Soluble Epoxide Hydrolase - Cuong, Nguyen Manh; Van, Doan Thi; Son, Ninh The; Cuong, To Dao; Khanh, Pham Ngoc; Binh, Nguyen Quoc; Thanh, Tran Thi Viet; Lee, Ji Sun; Jo, Ah Reum; Kim, Young Ho (Bulletin of the Korean Chemical Society, 2017)
KCI Citation Count: 3